Analysis and Counteraction of Ransomware Attacks Literature Review and Case Studies - Mariusz LAZARSKI (Communications of International Proceedings, 2025)
Ransomware attacks constitute one of the most critical and rapidly evolving threats in today’s cybersecurity landscape. This highly sophisticated form of malware can result in severe financial and operational losses, particularly for individuals and organizations that are insufficiently prepared to address such risks. The study explores detection techniques and classifies key countermeasures, emphasizing the significance of multilayered security architectures, robust data encryption, and regular backup strategies. Particular attention is devoted to the role of digital forensics, which is essential for data recovery, identifying attack sources, and designing effective prevention frameworks. Furthermore, the paper highlights the relevance of legal regulations and compliance procedures as crucial components in minimizing the risk of financial penalties and reputational damage. The analysis demonstrates that effective protection against ransomware requires an integrated approach combining advanced security technologies, well-designed organizational procedures, and modern tools driven by artificial intelligence and automation.
Keywords: Ransomware; digital forensics; countermeasures; cybersecurity.